Successful Treatment of Schwartz-Jampel Syndrome with Botulinum Toxin Type A - Panittra Suphatsathienkul; Kullasate Sakpichaisakul; Thanin Wechapinan; Objoon Trachoo; Sorawit Virawan; Rungsima Wanitphakdeedecha (Adis, Springer Healthcare, 2024)
Abstract Schwartz-Jampel syndrome (SJS) is a rare autosomal recessive disorder characterized by typical facial dysmorphism, generalized muscle stiffness, joint contracture, and skeletal abnormalities. This condition is caused by mutations in the heparan sulfate proteoglycan 2 (HSPG2) gene, which encodes perlecan, a component of the basement membrane. The management of patients with SJS primarily aims to alleviate symptoms related to muscle stiffness. In this report, we describe a male patient with SJS type 1A. Trio whole-exome sequencing identified a pathogenic mutation (NM_001291860.1: c.10897C>T; p.Arg3633Ter) and variants of unknown significance (NM_001291860.2: c.413+10G>T). The patient experienced difficulty in opening his eyes and mouth, which significantly limited his daily activities. Botulinum toxin A injection was administered and demonstrated significant clinical improvement after the treatment.